Vagal denervation inhibits the increase in pulmonary blood flow during partial lung aeration at birth. (14th February 2017) - Lang, Justin A. R.; Pearson, James T.; Binder‐Heschl, Corinna; Wallace, Megan J.; Siew, Melissa L.; Kitchen, Marcus J.; te Pas, Arjan B.; Lewis, Robert A.; Polglase, Graeme R.; Shirai, Mikiyasu; Hooper, Stuart B.
Abstract : Key points: Lung aeration at birth significantly increases pulmonary blood flow, which is unrelated to increased oxygenation or other spatial relationships that match ventilation to perfusion. Using simultaneous X‐ray imaging and angiography in near‐term rabbits, we investigated the relative contributions of the vagus nerve and oxygenation to the increase in pulmonary blood flow at birth. Vagal denervation inhibited the global increase in pulmonary blood flow induced by partial lung aeration, although high inspired oxygen concentrations can partially mitigate this effect. The results of the present study indicate that a vagal reflex may mediate a rapid global increase in pulmonary blood flow in response to partial lung aeration. Abstract: Air entry into the lungs at birth triggers major cardiovascular changes, including a large increase in pulmonary blood flow (PBF) that is not spatially related to regional lung aeration. To investigate the possible underlying role of a vagally‐mediated stimulus, we used simultaneous phase‐contrast X‐ray imaging and angiography in near‐term (30 days of gestation) vagotomized ( n =  15) or sham‐operated ( n =  15) rabbit kittens. Rabbits were imaged before ventilation, when one lung was ventilated (unilateral) with 100% nitrogen (N2 ), air or 100% oxygen (O2 ), and after all kittens were switched to unilateral ventilation in air and then ventilation of both lungs using air. Compared to control kittens, vagotomized kittens had little or no increase in PBF in both lungs following unilateral ventilation when ventilation occurred with 100% N2 or with air. However, relative PBF did increase in vagotomized animals ventilated with 100% O2, indicating the independent stimulatory effects of local oxygen concentration and autonomic innervation on the changes in PBF at birth. These findings demonstrate that vagal denervation inhibits the previously observed increase in PBF with partial lung aeration, although high inspired oxygen concentrations can partially mitigate this effect. Key points: Lung aeration at birth significantly increases pulmonary blood flow, which is unrelated to increased oxygenation or other spatial relationships that match ventilation to perfusion. Using simultaneous X‐ray imaging and angiography in near‐term rabbits, we investigated the relative contributions of the vagus nerve and oxygenation to the increase in pulmonary blood flow at birth. Vagal denervation inhibited the global increase in pulmonary blood flow induced by partial lung aeration, although high inspired oxygen concentrations can partially mitigate this effect. The results of the present study indicate that a vagal reflex may mediate a rapid global increase in pulmonary blood flow in response to partial lung aeration.